Relation of Oxidative Stress and Impaired Fibrinolysis with HDL Biogenesis in Indonesian Men with Metabolic Syndrome - Ida Paulina Sormin; Widjaja Lukito; Andi Wijaya; Suryani As'ad (The Prodia Education and Research Institute (PERI), 2010)
BACKGROUND: Biogenesis of HDL involves factors that regulate the synthesis, intravascular remodeling, and catabolism of HDL. Disturbance of these factors can lead to low concentration of HDL-C. Metabolic syndrome (MetS) is characterized by low concentration of high-density lipoprotein cholesterol (HDL-C). In MetS occur several pathological conditions including oxidative stress and impaired fibrinolysis, which contribute to the risk of atherosclerosis process. The correlation between oxidative stress and impaired fibrinolysis with HDL biogenesis dysfunction and its correlation with low concentration of HDL-C has not been well understood and therefore needs to be further investigated.METHODS: This study was an observational study with crosssectional design, involving 163 adult men, aged 25-60 years with metabolic syndrome. Concentration of apoA-1, prebeta-1 HDL, CETP, F2-isoprostan, PAI-1, and HDL-C were measured. The apo A1/HDL ratio indicated HDL maturation, whereas the CETP/HDL-C and CETP/TG ratios indicated HDL catabolism.RESULTS: The study showed that there were a positive correlation between PAI-1 with apoA1/HDL-C ratios (r=0.226, p=0.005) and a negative correlation with the CETP/TG ratios (r=-0.215, p=0.007), whereas F2-isoprostan did not have correlation with HDL biogenesis factors.CONCLUSIONS: We concluded that there was correlation between impaired fibrinolysis with decreased HDL maturation and there was increased HDL catabolism leading to low HDL-C concentration in men with metabolic syndrome.KEYWORDS: F2-isoprostan, PAI-1, apoA-1, prebeta-1 HDL, CETP, metabolic syndrome